THE USE OF A NEW APPROACH TO PREVENTION AND THERAPY OF ACUTE ARTERIAL HYPERTENSION WITH COMPLEX OF WELL-KNOWN DRUGS WITH VEGETABLE GLYCOSIDES (EXPERIMENTAL STUDY) - T. G. Tolstikova; I. V. Sorokina; A. O. Brisgalov; M. P. Dolgich; G. I. Lifshitz; M. V. Chvostov (Рациональная фармакотерапия в кардиологии)
Aim. To evaluate antihypertensive efficacy of nifedipine (N) and nifedipine complex (NC) in acute test in rats with adrenaline model of arterial hypertension. Material and methods. N is a conventional short acting formulation while NC is a new formulation of nifedipine in complex with glycyrrhizic acid. NC has an active substance 10 times less than N does in the same dose. Adrenaline which results in two times increase in blood pressure (BP) during 4 min was administered as a single i.v. dose (0,03 mg/kg) to normotensive unconscious male rats (body weight 190-220 g). NC and N were administered in the same dose (3,5 mg/kg) before and after adrenaline administration. Systolic BP recovering time was assessed. BP level was measured with direct method in carotid artery. Results. NC and N decreased in systolic BP in normotensive rats by 26 and 30% respectively. NC and N administered before adrenaline administration resulted in systolic BP recovering time reduction to 94,4 and 79,7 s respectively, which are less than this in control (204,8 s, р<0,001). Difference in time between NC and N is not significant (p<0,1). NC and N administered after adrenaline administration resulted in systolic BP recovering time reduction to 104,7 and 139 s respectively, which are also less than this in control (204,8 s, р<0,001). Difference in time between NC and N in this model is also not significant (p<0,1).  Conclusion. NC with contents of active substance 10 times less than in N showed antihypertensive efficacy similar with this in N. NC can be used for prevention and therapy of acute arterial hypertension.